1986
DOI: 10.1073/pnas.83.5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Metastable photoproducts from carbon monoxide myoglobin.

Abstract: The photoproduct of carbon monoxide myoglobin generated at 4 K and lower has a resonance Raman spectrum characteristic of a high-spin heme but in which the high-frequency core size-sensitive lines are at lower frequency than those in the deoxy preparation. Such differences are not detected in the photoproduct generated at higher temperatures (50 K) or in that generated at room temperature with 10-nsec pulses. The data indicate that at the low temperature (4 K), the heme in the photoproduct is not fully relaxed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
(31 reference statements)
1
29
0
Order By: Relevance
“…Raman spectroscopy offers support for the hindered mobility of the heme iron in the photoproduct Mb* at low temperatures. From the shifts of Raman lines in the high-frequency region ("1500 cm-'), Rousseau and Argade (8) concluded that the heme core of Mb* is expanded compared to deoxyMb (2.027 versus 2.020 A at 4.2 K) (8). This expansion can be explained by the increased repulsion between the occupied (d.2-y2) orbital of the high-spin iron and the pyrrole nitrogen orbitals because of incomplete relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy offers support for the hindered mobility of the heme iron in the photoproduct Mb* at low temperatures. From the shifts of Raman lines in the high-frequency region ("1500 cm-'), Rousseau and Argade (8) concluded that the heme core of Mb* is expanded compared to deoxyMb (2.027 versus 2.020 A at 4.2 K) (8). This expansion can be explained by the increased repulsion between the occupied (d.2-y2) orbital of the high-spin iron and the pyrrole nitrogen orbitals because of incomplete relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The rate coefficient K*(T) does not follow an Arrhenius relation but can be described by K*(T) = A*e-[E*/RTf. [8] The relaxation parameters for MbCO in glycerol/buffer, pH 6.8, were determined from fitting the rebinding kinetics between 160 and 210 K by Eqs. 7 and 8 (13).…”
Section: The Protein Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Important in the context of these studies is that hemoproteins are photosensitive, leading to a wide range of time-resolved optical and X-ray spectroscopic studies ranging from milliseconds to femtoseconds. [15][16][17][18][19][20][21][22][23][24][25][26][27] In these experiments, the biological function of ligand detachment from the heme is triggered by an optical (so-called pump) pulse, while the evolution of the system is probed by a second (typically optical or X-ray) pulse, with a tunable time delay with respect to the pump pulse. While optical tools can reach femtosecond resolution they do not provide direct structural information.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of v2 at cryogenic temperatures corroborates these results. Rousseau and Argade (1986) found that the position of v2 was -4 em-• lower in the metastable photoproduct of MbCO. They interpreted this as an indication of an expanded heme core-size and further evidence of an unrelaxed heme.…”
Section: Cryogenic Studiesmentioning
confidence: 94%